Creativity management within the aesthetical situation regarding the in-real or digital form of participation in arts: art receivers’ perspective - Szostak, Michał; Sułkowski, Łukasz (Creativity Studies, 2024)
Because digitalisation of the aesthetical experience, a process speeded up by the not-yet-finished COVID-19 pandemic, should be considered in the context of growth or loss of artistry/creativity, this paper aims to assess the influence of the participation form in the aesthetical situation by receivers on the level of artistry/creativity potential loss. Assessment of the quality of participation by the receivers in each of five types of arts (musical arts, performing arts, literary arts, audio-visual arts, visual arts) was done using the same ten criteria for each type of art: satisfaction, pleasure, engagement, the possibility of experiencing catharsis, contact with the artwork itself, contact with the performer itself, comfort of participation, possibilities of shaping the aesthetical experience, own motivation to participate, easiness of participation. The literature review was run using NVivo Pro software. Data analysis (n = 221) was executed using IBM SPSS and Microsoft Excel. Answering the research hypotheses: H1) the digital form of participation in arts determines the level of quality of participation in the aesthetical situation by receivers; H2) the form of participation in art shapes the level of quality of participation in the aesthetical situation by receivers of each type of art differently: in musical arts, performing arts, literary arts and visual arts, in-real participation gives higher quality than digital participation; in audio-visual arts, in-real participation gives lower quality than digital participation. The research results may be helpful for: art creators wanting to choose the optimal way of distributing their artworks; art managers to better understand art receivers’ perspectives and their opinion about participation in arts in real or digitally; art receivers to compare their private opinion about the ways of participation in arts with the general opinion of art receivers.